1979
DOI: 10.1002/qua.560160312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annelation by benzene ring on electronic absorption spectra and on character of the singlet π‐π* transitions at polynuclear p‐quinones

Abstract: Aromatic polynuclear pquinones and their derivatives have been studied using their electronic absorption and luminescence spectra and their basicity. The data were used to provide a basis for the study of the relationships between the structure and the spectral characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…12 Kunavin and Shvekhgeimer reported that the lr3(n,z*) state energies of dicarbonyl compounds depend both on the presence of vinyl groups conjugated with carbonyl groups and on the mutual position of carbonyl groups in a molecule.lo6 As is seen in Figure 8, the energy levels of the lowest order spin-orbit and vibronic perturbations of the singlet and triplet states. Hartmann and Lorenz first showed that the carbonyl group in quinones interrupted the n-electron delocalization and that the position of the first singlet ~tn* transition was determined by the size of the aromatic subsystem ( m or n in Q [ n~, n l ) .~~ Nepras and Titz have attempted to provide a quantitative interpretation for Hartmann's observation using a PPP method.12 The l(n,z*) electronic spectra have been interpreted in terms of the local and charge-transfer transitions of the aromatic subsystem.…”
Section: V Excited-state Ordering and Emitting Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Kunavin and Shvekhgeimer reported that the lr3(n,z*) state energies of dicarbonyl compounds depend both on the presence of vinyl groups conjugated with carbonyl groups and on the mutual position of carbonyl groups in a molecule.lo6 As is seen in Figure 8, the energy levels of the lowest order spin-orbit and vibronic perturbations of the singlet and triplet states. Hartmann and Lorenz first showed that the carbonyl group in quinones interrupted the n-electron delocalization and that the position of the first singlet ~tn* transition was determined by the size of the aromatic subsystem ( m or n in Q [ n~, n l ) .~~ Nepras and Titz have attempted to provide a quantitative interpretation for Hartmann's observation using a PPP method.12 The l(n,z*) electronic spectra have been interpreted in terms of the local and charge-transfer transitions of the aromatic subsystem.…”
Section: V Excited-state Ordering and Emitting Statesmentioning
confidence: 99%
“…66 Nepras and Titz have attempted to provide a quantitative interpretation for Hartmann's observation using a PPP method. 12 The l{it,7i*) electronic spectra have been interpreted in terms of the local and charge-transfer transitions of the aromatic subsystem. They stated that the lowest \n,n*) state energies in acenequinones depend not only on the size of the larger aromatic subsystem but also on the size of smaller one.…”
Section: Other Higher Linear Para Quinonesmentioning
confidence: 99%
See 2 more Smart Citations